Advancing time-since-interval estimation for clandestine graves: a forensic ecogenomics perspective into burial and translocation timelines using massively parallel sequencing - de Bruyn, Cherene; Scott, Kirstie; Panter, Heather; Bezombes, Frederic; Ralebitso-Senior, Komang (Frontiers in Microbiology, 2025)
Forensic taphonomy and entomology has focused on estimating the post-mortem interval (PMI), particularly for surface depositions, using human cadavers and other mammalian models by considering morphological changes of the body and insect activity during decomposition. The PMI is crucial in forensic investigations as it provides key information regarding the victim’s identity, the circumstances of their death and can confirm or refute a suspect’s alibi. Gravesoil microbial communities are a potential tool that can complement traditional approaches to detect and confirm the presence of human remains in clandestine burials, aiding forensic investigations. The estimation of the time-since-burial (post-burial interval; PBI), and the time-since-translocation (post-translocation interval; PTI), a new concept, have potential to aid clandestine grave location but have received relatively little attention in forensic ecology research. Advances in massively parallel sequencing (MPS) provide a high-throughput means to estimate PBI and PTI by characterising soil microbial communities in graves with remains, from early to skeletal stages of decomposition, or where remains have been intentionally removed from crime scenes and relocated. This review presents a perspective on the use of the soil microbiome as an indicator for post-mortem time-since-interval estimations, with specific focus on the PBI and PTI. In addition, it provides a framework, supported within forensic ecogenomics, on how the PBI and PTI can be used as a forensic tool complemented by MPS. The review highlights the need for further research to validate microbial community analysis across diverse biogeographical regions to enhance its precision and reliability as a forensic investigative tool. Such validation could potentially enhance the accuracy of post-burial and post-translocation interval estimations, ultimately improving methods for clandestine grave identification.